Posterior circulation ischemic stroke not involving the brainstem is associated with cardiovascular autonomic dysfunction - Wang, Ruihao; Kohrmann, Martin; Kollmar, Rainer; Köhn, Julia; Schwab, Stefan; Kallmünzer, Bernd; Hilz, Max-Josef (European Journal of Neurology, 2022)
Background and purpose Ischemic stroke may induce cardiovascular autonomic dysfunction, but most previous studies have included patients with anterior circulation ischemic stroke or brainstem stroke. It remains unclear whether posterior circulation ischemic stroke (PCIS) without brainstem involvement also compromises cardiovascular autonomic modulation (CAM). Therefore, we aimed to assess CAM in PCIS patients with and without brainstem involvement. Methods In four subgroups of 61 PCIS patients (14 occipital lobe, 16 thalamic, 12 cerebellar, and 19 brainstem strokes) and 30 healthy controls, we recorded RR intervals (RRIs), systolic (SBP) and diastolic blood pressure (DBP), and respiration at supine rest during the first week after stroke onset. We calculated parameters reflecting total CAM (RRI-standard deviation [RRI-SD], RRI-total powers), predominantly sympathetic CAM (RRI-low-frequency [LF] powers and SBP-LF powers] and parasympathetic CAM (root mean square of successive RRI differences [RMSSD], RRI-high-frequency [HF] powers), sympathetic-parasympathetic balance (RRI-LF/HF ratios), and baroreflex sensitivity (BRS). Values were compared among the four PCIS groups and controls using one-way ANOVA Kruskal-Wallis tests, with post-hoc analyses. Significance was assumed for p < 0.05. Results In each PCIS subgroup, values for RRI, RRI-SD, RMSSD, RRI-HF powers, and BRS were significantly lower, while SBP-LF powers were higher than in the controls. Only in patients with occipital lobe stroke were RRI-LF/HF ratios significantly higher than in controls. Otherwise, autonomic variables did not differ among the four PCIS subgroups. Conclusions During the first week after stroke onset, our PCIS patients with occipital lobe, thalamic, cerebellar, or brainstem strokes all had reduced cardiovagal modulation, compromised baroreflex, and increased peripheral sympathetic modulation. The RRI-LF/HF ratios suggest that sympathetic predominance is slightly more prominent after occipital lobe stroke. PCIS may trigger cardiovascular autonomic dysfunction even without brainstem involvement.
CRIS-Team WoS Importer:2022-06-24